Trade Cycles and the Effort to Anticipate - Selden, G. C. (Quarterly Journal of Economics, 1902)
Journal Article Trade Cycles and the Effort to Anticipate Get access G. C. Selden G. C. Selden Chicago, July 30, 1901 Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 16, Issue 2, February 1902, Pages 293–310, https://doi.org/10.2307/1882747 Published: 01 February 1902